EDUKASI DAN PELATIHAN SENAM ANTI HIPERTENSI PADA LANSIA DALAM UPAYA PENCEGAHAN PENYAKIT HIPERTENSI DI WILAYAH KERJA PUSKESMAS SENGETI KABUPATEN MUARO JAMBI - Hubaybah Hubaybah; Adelina Fitri; Oka Lesmana; Fitria Eka Putri (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Hypertension disease in the elderly can affect the quality of life. This disease causes various complications that require much money; therefore, Hypertension exercises can help reduce complications from Hypertension. The purpose of this community service was for the community, especially the elderly, to know and apply how to do Hypertension exercises. This community service partner is the elderly in the Sengeti Health Center working area, Muaro Jambi Regency, which was carried out through education and training in Hypertension exercises. The results of this activity obtained an increase in knowledge and understanding of elderly participants from 30% to 70% at the end of the activity. The facts prove the importance of health counselling through education and training in Hypertension exercises to reduce the risk of complications of Hypertension disease.